HADITH AND PROPHET MUHAMMAD AUTHORITY: Understanding of Jonathan A.C. Brown - Nafisah, Lailiyatun (RIWAYAH, 2022)
Hadith is frequently the subject of research by Muslim academics and Westerners. Both Muslim academics and orientalists have debated the legitimacy of the hadith for a long time. Jonathan AC Brown is a western Muslim scholar who contributes to rationally explaining the study of hadith so that it is easily accepted by beginners; his work demonstrates his commitment to the study of Islamic studies. This study follows a library research approach in which Jonathan Brown's book "Hadith: Muhammad's Legacy in the Medieval and Modern World" is utilized as the primary reference source, which is then supplemented with scholarly publications and journals on Jonathan Brown. The author used the descriptive analysis technique. According to the findings of this study, a hadith is a report about the Prophet consisting of the main text that describes his words or actions, the way of transmission (isnad) that serves to convey, and finally the giver. The authority of Muhammad is that of a Prophet who functions as a teacher, leader, and role model, as well as someone who has knowledge of the future. However, because the Prophet was an ordinary person, he did not have full authority in some matters.[Hadis dan Otoritas Nabi Muhammad: Pemahaman Jonathan A.C. Brown. Hadis sering menjadi bahan kajian yang tidak hanya dilakukan oleh sarjana muslim, namun juga barat. Berbagai pro dan kontra akan keaslian hadis telah lama berkembang, baik sarjana muslim maupun orientalis. Jonathan A.C Brown, merupakan sarjana muslim barat yang berkontribusi dalam menjelaskan kajian hadis secara rasional sehingga mudah diterima kaum pemula, karya yang dihasilkannya merupakan bukti keseriusan dalam kajian studies islamic.  Penelitian ini merupakan model penelitian kepustakaan (library reseach) dimana, buku “Hadith: Muhammad’s legacy in the medieval and modern world” Brown dijadikan sebagai sumber rujukan utama, kemudian didukung oleh karya ilmiah dan jurnal yang berkaitan dengan Jonathan Brown. Penulis menggunakan metode analisis deskriptif. Hasil penelitian ini menunjukan bahwa hadis adalah adalah laporan tentang Nabi, yang terdiri dari teks utama untuk menjelaskan kata- kata atau tindakannya, rantai transmisi (isnad) yang berufngsi untuk mengkomunikasikan, kemudian penyampai. Otoritas Muhammad merupakan seorang Nabi yang memiliki peran sebagai guru, panutan, dan teladan, dan seseorang yang mampu memiliki akses mengetahui masa depan. Akan tetapi Nabi adalah seorang manusia biasa sehingga tidak secara keseluruhan menjadi otoritatif dalam beberapa hal.]